1998
DOI: 10.1023/a:1008327301372
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and prognosis in a series of primary extranodal lymphomas of the ocular adnexa

Abstract: Regardless of histology, prognosis was excellent when surgery plus RT was adopted, and CT seems to be a valid alternative to RT. Surgery alone may be sub-optimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
2
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 11 publications
7
43
2
2
Order By: Relevance
“…5,18 Indeed, follicular lymphoma was not diagnosed in the present study, while studies of Western populations report follicular lymphoma is the second most common subtype. 6,19 A high MALT lymphoma frequency in the current and previous studies suggests extranodal predominance might be a characteristic of malignant lymphomas in Korea. Such findings might be related to the high prevalence of Helicobacter pylori infection in Korea.…”
Section: Discussionsupporting
confidence: 55%
“…5,18 Indeed, follicular lymphoma was not diagnosed in the present study, while studies of Western populations report follicular lymphoma is the second most common subtype. 6,19 A high MALT lymphoma frequency in the current and previous studies suggests extranodal predominance might be a characteristic of malignant lymphomas in Korea. Such findings might be related to the high prevalence of Helicobacter pylori infection in Korea.…”
Section: Discussionsupporting
confidence: 55%
“…Several case series have included patients who did not undergo any additional treatment after surgical excision. 4,[11][12][13]48,[61][62][63][64][65] Although several patients may remain free of recurrence during the subsequent surveillance period, we, like most authors, conclude that this approach is inferior.…”
Section: Surgical Resectionmentioning
confidence: 45%
“…18,42 However, this approach has not been fully evaluated; the outcome was clearly indicated for only 8 patients in these reports. 13,36,45,46,91 Two (25%) of these 8 patients did not experience relapse, 3 (37.5%) experienced local recurrence at the initial ophthalmologic site, and 3 (37.5%) contracted disseminated extra-ophthalmologic disease. More recently, Matsuo and Yoshino 92 reported a series of 8 patients with MALT lymphoma who did not undergo complementary treatment after surgical biopsy, 7 of whom experienced spontaneous tumor regression between 1 and 5 years.…”
Section: Surgical Excision and Wait-and-see Policymentioning
confidence: 99%
“…Metastatic involvement of the eye or central nervous system is rarely observed with low-grade ocular adnexal lymphoma, and central nervous system (CNS) prophylaxis with radiotherapy or chemotherapy is considered unnecessary. 37 A number of studies 11,13,18,16,27,30,36,39,[41][42][43][44][45][46][47]83,91 have reported treatment with chemotherapy alone or in combination with other modalities, but few have reported the response rates obtained with these treatments. 11,46,47,84,85 Lee et al 47 reported 3 patients who underwent CHOP chemotherapy, 2 of whom experienced complete remission.…”
Section: Chemotherapy Regimens and Oalmentioning
confidence: 99%
See 1 more Smart Citation